2011
DOI: 10.1186/1479-5876-9-133
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and targeting of phosphatidylinositol-3 kinase (PI3K) and mammalian target of rapamycin (mTOR) in renal cell cancer

Abstract: BackgroundPI3K and mTOR are key components of signal transduction pathways critical for cell survival. Numerous PI3K inhibitors have entered clinical trials, while mTOR is the target of approved drugs for metastatic renal cell carcinoma (RCC). We characterized expression of p85 and p110α PI3K subunits and mTOR in RCC specimens and assessed pharmacologic co-targeting of these molecules in vitro.MethodsWe employed tissue microarrays containing 330 nephrectomy cases using a novel immunofluorescence-based method o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 45 publications
3
34
0
Order By: Relevance
“…We previously reported that combined treatment with Rapa and CN-A was also effective in inhibiting the growth of MDA-MB231 cells (17). As with recent reports (28,29), the potent well-known PI3K inhibitor LY294002 inhibited Rapa-induced phosphorylation of Akt (Ser473) (Fig. 7B) and was able to enhance the Rapa-induced growth inhibition of MCF-7 cells in our culture conditions (Fig.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We previously reported that combined treatment with Rapa and CN-A was also effective in inhibiting the growth of MDA-MB231 cells (17). As with recent reports (28,29), the potent well-known PI3K inhibitor LY294002 inhibited Rapa-induced phosphorylation of Akt (Ser473) (Fig. 7B) and was able to enhance the Rapa-induced growth inhibition of MCF-7 cells in our culture conditions (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…We next examined the effects of a potent PI3K inhibitor LY294002 on Rapa-induced phosphorylation of Akt (Ser473) and Rapa-induced growth inhibition of MCF-7 cells. In agreement with previous reports (28,29), LY294002 (3 µM) alone significantly inhibited phosphorylation of both Akt (Ser473) and p70S6K (Fig. 7B).…”
Section: Cn-a Suppresses Rapa-induced Phosphorylation Of Akt and Enhasupporting
confidence: 93%
“…This pathway is a prime target in radiotherapy, and inhibition of this cascade can induce autophagy and enhance the radiosensitivity of tumor cells. In fact, the dual PI3K/mTOR inhibitor NVP-BEZ235 exhibits promising effects against various tumors [42][43][44][45] . However, to date, research has not yet focused on the radiosensitization efficacy of NVP-BEZ235 in GSCs, which are a small subpopulation of GBM that exhibit higher radioresistance.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, researchers have detected low PTEN expression, and high expression of PI3K/mTOR, in clear cell RCC [97,98]. Further, high PI3K/mTOR expression seems to be associated with poorer prognosis [99,100]. Given the importance of mTOR for RCC, great progress has been made in targeting mTOR.…”
Section: Reviewmentioning
confidence: 99%